2023
DOI: 10.1128/mbio.02478-22
|View full text |Cite
|
Sign up to set email alerts
|

Purine Nucleosides Interfere with c-di-AMP Levels and Act as Adjuvants To Re-Sensitize MRSA To β-Lactam Antibiotics

Abstract: The clinical burden of infections caused by antimicrobial resistant (AMR) pathogens is a leading threat to public health. Maintaining the effectiveness of existing antimicrobial drugs or finding ways to reintroduce drugs to which resistance is widespread is an important part of efforts to address the AMR crisis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 66 publications
9
27
0
Order By: Relevance
“…Single-cell time-lapse microscopy revealed that the increased c-di-AMP level in the ∆gdpP mutant did not impact its generation time indicating that the smaller cell volume is responsible for the reduced growth detected by OD measurements. These findings are in line with a recent study showing an increase in cell size in S. aureus JE2 correlated with an increase in OD (29). The ∆gdpP/∆pde2 and dacA G206S mutants showed a longer generation time indicating a c-di-AMP optimum concentration range for unimpaired growth.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Single-cell time-lapse microscopy revealed that the increased c-di-AMP level in the ∆gdpP mutant did not impact its generation time indicating that the smaller cell volume is responsible for the reduced growth detected by OD measurements. These findings are in line with a recent study showing an increase in cell size in S. aureus JE2 correlated with an increase in OD (29). The ∆gdpP/∆pde2 and dacA G206S mutants showed a longer generation time indicating a c-di-AMP optimum concentration range for unimpaired growth.…”
Section: Discussionsupporting
confidence: 92%
“…However, the majority of these mecA-negative clinical isolates had acquired mutations in gdpP, indicating a clinical relevance of strains with increased c-di-AMP levels. Confirming earlier studies, we found drastically increased MICs for the beta-lactam oxacillin in the ΔgdpP and ΔgdpP/Δpde2 mutants and a decreased MIC in the dacA G206S mutant (3,8,9,29,33). In clinics, cephalosporins are often used to treat MRSA infections as they exhibit high affinity to the MRSA-specific PBP2a.…”
Section: Discussionsupporting
confidence: 89%
“…Extrapolating from previous data showing that purine metabolism controls β-lactam resistance (26, 41, 5356), we turned our attention to the PPP, which produces ribose-5-P, a major substrate for purine and pyrimidine biosynthesis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…We and others have previously reported that purine nucleotide homeostasis plays a key role in the regulation of β-lactam resistance in MRSA (4953). Mutations in the pur operon and purine salvage pathway were associated with increased resistance, whereas exposure of MRSA to the purine nucleosides guanosine or xanthosine reduced β-lactam resistance (53).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation